Impact of pneumococcal conjugate vaccines on healthcare utilization and direct costs for otitis media in children ≤2 years of age in two Swedish regions - Mark Edmondson-Jones; Therese Dibbern; Marcus Hultberg; Bengt Anell; Emma Medin; Yang Feng; Carla Talarico (Taylor & Francis Group, 2022)
In Sweden, the 7-valent pneumococcal conjugate vaccine (PCV7) was introduced in 2009 and replaced by the pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) or the 13-valent PCV (PCV13) from late 2009. We assessed the impact of PCVs on rates of antibiotic prescribing, tympanostomy tube placement (TTP), and healthcare resource utilization and direct costs of physician-diagnosed otitis media/acute otitis media (OM) in children ≤2 years of age living in Skåne (PCV7 then PHiD-CV) or Västra Götalandsregionen (VGR; PCV7 then PCV13). Retrospective cohort study using linked patient-level data from national and regional (Skåne and VGR) healthcare databases in Sweden from July 1, 2005, to December 31, 2013 (NCT02742753). Descriptive time-series analyses showed antibiotic prescriptions and TTP incidence declined after PHiD-CV/PCV13 introduction versus the pre-PCV period. The annualized mean frequencies of antibiotic use, primary care visits, outpatient visits, TTP and myringotomy procedures all decreased after PHiD-CV/PCV13 compared with pre-PCV cohorts. Annualized mean total OM-associated healthcare costs decreased in the PCV7 versus pre-PCV cohorts by 20.0% in Skåne and 10.2% in VGR, and further declined in the PHiD-CV and PCV13 cohorts (20.7% and 15.3%, respectively, relative to the PCV7 cohort), although the duration of PCV7 use differed between regions. Decreases in adjusted annualized cost ratios between cohorts per child susceptible to OM were statistically significant after PCV7 introduction and again with either PHiD-CV or PCV13 introduction in both regions. Following sequential PCV introduction, OM-related healthcare utilization and associated costs decreased in the study regions in Sweden. PLAIN LANGUAGE SUMMARY What is the context? Otitis media is one of the most frequent reasons for healthcare visits and antibiotic use among young children. Although it is considered as a mild illness, the overall economic burden is substantial due to its high frequency. Otitis media can be caused by different bacteria including Streptococcus pneumoniae, which is also responsible for pneumonia and meningitis. Pneumococcal conjugate vaccines Prevenar (Pfizer Inc.), Synflorix (GSK), and Prevenar 13 (Pfizer Inc.) protect against pneumococcal diseases and reduce its occurrence. However, it is not known how the routine use of these vaccines may affect otitis media-related healthcare resources and costs. What is new? In this study, we assessed trends in rates of healthcare utilization and associated costs due to otitis media in young children before (2005-2008) and after (2009-2013) use of pneumococcal conjugate vaccines. The study was conducted in two Swedish regions; one used Prevenar then Synflorix, while the other used Prevenar then Prevenar 13. We found that compared to the period before pneumococcal conjugate vaccine implementation, the post-pneumococcal conjugate vaccine period was associated with: A decrease in otitis media-related antibiotic prescriptions and surgical procedures in both regions. A decrease in the annual frequency of otitis media related antibiotic use, primary care and outpatient visits, and surgical procedures. A significant reduction in otitis media-related healthcare costs in both regions. What is the impact on current thinking? The use of pneumococcal conjugate vaccines effectively reduces healthcare utilization and resources associated with otitis media. This indirect effect on the reduction of otitis media burden provides further benefit to the implementation of pneumococcal vaccination.